국내 퇴적 지반의 전단파 속도 평가를 위한 탄성파 피에조콘 관입 시험의 종합적 활용 - 정경자; 선창국; 김홍종; 정종홍 (물리탐사, 9(3), 2006)
It has been widely known that the seismic piezo-cone penetration test (SCPTu) is one of the most usefultechniques for investigating the geotechnical characteristics such as static and dynamic soil properties. As practicalapplications in Korea, SCPTu was carried out at two sites in Busan and four sites in Incheon, which are mainly composedof alluvial or marine soil deposits. From the SCPTu waveform data obtained from the testing sites, the first arrival timesof shear waves and the corresponding time differences with depth were determined using the cross-over method, andthe shear wave velocity (VSlaw. Comparing the determined VS profile with the cone tip resistance (qt) profile, both trends of profiles with depthwere similar. For the application of the conventional CPTu to earthquake engineering practices, the correlations betweenVS and CPTu data were deduced based on the SCPTu results. For the empirical evaluation of VS for all soils togetherwith clays and sands which are classified unambiguously in this study by the soil behavior type classification index (IC),the authors suggested the VS-CPTu data correlations expressed as a function of four parameters, qt, fs, σ'v0 and Bq,determined by multiple statistical regression modeling. Despite the incompatible strain levels of the downhole seismictest during SCPTu and the conventional CPTu, it is shown that the VS-CPTu data correlations for all soils, clays andsands suggested in this study is applicable to thepreliminary estimation of VS for the soil deposits at apart in Korea and is more reliable than the previouscorrelations proposed by other researchers. KCI Citation Count: 2